Efficacy and safety of exenatide versus insulin in type 2 diabetes mellitus: Systematic review and meta-analysis - Bao-Ju Chen; Ju Chuko; Chi-Hua Tung; Kuang-Yu Hu (International Journal of Management, Economics and Social Sciences (IJMESS), 2019)
Exenatide is one of a new class of medications (incretin mimetics) for the treatment of type 2 diabetes mellitus and was approved in April 2005 by the U.S. Food and Drug Administration. We undertook a systematic review and meta-analysis of exenatide therapy compared to both placebo and insulin therapy in terms of main efficacy parameters and safety. We searched PubMed for randomized controlled clinical studies of type 2 diabetes mellitus of at least 12 weeks' duration published from June 2003 to July 2010. Exenatide reduced the mean differences of HbA1c comparing with both placebo (-0.88% [95% CI -0.98 to -0.79]) and insulin (0.05% [95% CI -0.11 to 0.21]). And, mean differences of body weight were reduced for exenatide comparing with both placebo (-1.18 kg [95% CI -1.44 to -0.93]) and insulin (-5.42 kg [95% CI -5.89 to -4.95]). Exenatide has beneficial effects on glycemic control and is relatively safe in terms of the adverse events studied. The glycemic control effects of exenatide and insulin are similar, but the body weight reduction effects of exenatide are greater. This indicates that exenatide provides another choice for type 2 DM patients who have weight control problems.
Keywords: I10; 330; Exenatide; diabetes mellitus; meta-analysis; evidence based medicine